2019
DOI: 10.1016/j.celrep.2019.07.076
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling the DSB End-Protecting and CSR-Promoting Functions of 53BP1

Abstract: Sundaravinayagam et al. (2019) uncovered a critical role of 53BP1 in class switch recombination in B cells beyond its role in limiting end resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…On the other hand, in 53bp1 −/− cells the requirement for CtIP to exclude 53BP1/Rif1 becomes minimal as resection suppression by Rif1 has been canceled out. Consistent with the minimal effect of resection on CSR efficiency we observed in 53bp1 −/− cells, a recent report revealed that resection can be largely uncoupled with CSR ( Sundaravinayagam et al, 2019 ) and suggested that higher order chromatin structure by 53BP1 oligomerization is essential to enforce the 3-D architecture of IgH locus for efficient class switching ( Dong et al, 2015 ; Fernandez and Chaudhuri, 2019 ). In this context, resection inhibition in 53bp1 −/− cells by either Mre11/CtIP silencing or ATM ablation did not change A-EJ efficiency, as the requisite IgH loops for efficient CSR has already greatly collapsed ( Wuerffel et al, 2007 ; Feldman et al, 2017 ; Zhang et al, 2019 ) ( Cortizas et al, 2013 ).…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, in 53bp1 −/− cells the requirement for CtIP to exclude 53BP1/Rif1 becomes minimal as resection suppression by Rif1 has been canceled out. Consistent with the minimal effect of resection on CSR efficiency we observed in 53bp1 −/− cells, a recent report revealed that resection can be largely uncoupled with CSR ( Sundaravinayagam et al, 2019 ) and suggested that higher order chromatin structure by 53BP1 oligomerization is essential to enforce the 3-D architecture of IgH locus for efficient class switching ( Dong et al, 2015 ; Fernandez and Chaudhuri, 2019 ). In this context, resection inhibition in 53bp1 −/− cells by either Mre11/CtIP silencing or ATM ablation did not change A-EJ efficiency, as the requisite IgH loops for efficient CSR has already greatly collapsed ( Wuerffel et al, 2007 ; Feldman et al, 2017 ; Zhang et al, 2019 ) ( Cortizas et al, 2013 ).…”
Section: Discussionsupporting
confidence: 89%